Enhancing motor cortical theta and gamma oscillations using closed-loop phase-dependent optogenetic stimulation - Myatt, JL (2024)
Neuronal oscillations are a prominent feature of motor cortical local field potentials (LFPs) and abnormalities in oscillatory activity have been linked to several disorders. Theta-modulated gamma-frequency pulses of alternating current stimulation are known to modulate motor learning in humans; however, it is unclear how these frequencies modulate motor cortical activity at the cellular microcircuit level.